A Note on Enforcement Uncertainty and Taxpayer Compliance - Reinganum, Jennifer F.; Wilde, Louis L. (Quarterly Journal of Economics, 1988)
Jennifer F. Reinganum, Louis L. Wilde; A Note on Enforcement Uncertainty and Taxpayer Compliance*, The Quarterly Journal of Economics, Volume 103, Issue 4,